2018
DOI: 10.1002/biof.1462
|View full text |Cite
|
Sign up to set email alerts
|

Rhein reverses doxorubicin resistance in SMMC‐7721 liver cancer cells by inhibiting energy metabolism and inducing mitochondrial permeability transition pore opening

Abstract: Rhein, a monomeric anthraquinone obtained from the plant herb species Polygonum multiflorum and P. cuspidatum, has been proposed to have anticancer activity. This activity has been suggested to be associated with mitochondrial injury due to the induction of mitochondrial permeability transition pore (mPTP) opening. In this study, the effects of 5–80 μM rhein on cell viability, half‐maximal inhibitory concentration (IC50 value), resistance index, and apoptosis were assessed in the liver cancer cell lines SMMC‐7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…Further experiments have confirmed that Ginsenoside can slow down mitochondrial injury and IRI by inhibiting the CypD pathway [62], and in mouse and human liver tissues, C31, a small molecule inhibitor of CypD, has a high affinity for CypD, which can reduce calcium ion-induced mitochondrial swelling and destruction by blocking the opening of mPTP to play a role in protecting the liver from IRI [19]. Although rhein can induce the opening of mPTP to cause necrosis and apoptosis of hepatocytes, Oxidative Medicine and Cellular Longevity CsA can combine with CypD to reduce the toxic effect of rhein by inhibiting the opening of mPTP [63]. Besides, DS44170716, a small-molecule compound, has a significant protective effect on calcium-mediated mitochondrial swelling, and its protective effect is similar to that of CsA.…”
Section: Mptp and Mitophagymentioning
confidence: 99%
“…Further experiments have confirmed that Ginsenoside can slow down mitochondrial injury and IRI by inhibiting the CypD pathway [62], and in mouse and human liver tissues, C31, a small molecule inhibitor of CypD, has a high affinity for CypD, which can reduce calcium ion-induced mitochondrial swelling and destruction by blocking the opening of mPTP to play a role in protecting the liver from IRI [19]. Although rhein can induce the opening of mPTP to cause necrosis and apoptosis of hepatocytes, Oxidative Medicine and Cellular Longevity CsA can combine with CypD to reduce the toxic effect of rhein by inhibiting the opening of mPTP [63]. Besides, DS44170716, a small-molecule compound, has a significant protective effect on calcium-mediated mitochondrial swelling, and its protective effect is similar to that of CsA.…”
Section: Mptp and Mitophagymentioning
confidence: 99%
“…In vitro Caco-2 p-ERK1/2↑ (at higher concentrations of rhein) [150] In vitro HT29, HCT116, Colo205, SW620 HIF-1α↓, PD-L1↓, VEGF↓, COX-2↓, galectin-1↓ [98] In vitro HCT116, SW620 p-STAT3↓ [151] Glioma In vitro F98 ERK1/2↓ [152] In vitro T98G, U87, U251 Ac-K100↑, NDRG1↑ [153] Leukemia In vivo EU-1 injected SCID mice MDM2↓, p53↑ [154] In vitro HL-60 Cleaved caspase↑, cleaved PARP↑, cleaved Bid↑, ∆Ψm↓ [145] In vitro NB4 p-ERK↑, Caspase-3↑ [155] Liver cancer In vitro and in vivo HepG2, HepG2 injected BALB/c-nu mice β-catenin↓, S phase arrest↑ [111] In vitro HepG2 CD95↑, p53↑, p21/WAF↑, mCD95L↑, sCD95L↑ [96] In vitro BEL-7402 c-Myc↓, Caspase-3↑, S phase arrest↑ [54] In vitro SMMC-7721, SMMC-7721/DOX ATP synthesis↓, inner ∆Ψm↓ [156] In vitro HepG2, Huh7 ROS↑, p-c-Jun↑, Caspase-3↑ [55] Lung cancer In vitro and in vivo PC-9, H460, A549, H460 xenograft mice STAT3↓, Bax↑, Bcl-2↓, G2/M phase arrest↑ [157] In vitro A549 p-PI3K↓, Akt↓, mTOR↓, Bcl-2↓ [158] In vitro A549 G0/G1 phase arrest↑, GADD153↑, GRP78↑, Cyt c↑,…”
Section: Colon Cancermentioning
confidence: 99%
“…Rhein-mediated modulation of phosphorylation of Akt and FOXO3a induced Bim secretion and caused apoptosis in HepG2 cells [144]. It was shown that rhein also incited the release of mitochondrial Cyt c and hindered the synthesis of ATP, which induced apoptosis due to the loss of mitochondrial membrane potential in HepaRG cells and SMMC-7721/DOX cells, respectively [97,156]. In another study, it was reported that the proliferation of hepatocellular cells, BEL-7402 was significantly decreased by rhein via regulation of caspase-3 and oncogene c-Myc [54].…”
Section: Liver Cancermentioning
confidence: 99%
“…With the deepening of research, it is believed that more natural products that can regulate the mitochondria have the potential to be used in treating diseases, which is of utmost importance. Oxidative Medicine and Cellular Longevity [44] Oxidative stress Bulbine frutescens [37] Bullfrog oil [38] Orientin [40] Asparanin A [42] Gracillin [44] Apoptosis Bulbine frutescens [37] Orientin [40] Licochalcone A [41] Asparanin A [42] Parameritannin A-2 [43] Cernumidine [45] Mitochondrial membrane potential imbalance Bullfrog oil [38] Rhein [39] Asparanin A [42] Cernumidine [45] Neurodegenerative diseases…”
Section: Resultsmentioning
confidence: 99%